Tinnitus perception mediates the relationship between physiological and psychological problems among patients. Issue 3 (18th July 2019) - Abbas, Jaffar; Aqeel, Muhammad; Jaffar, A.; Nurunnabi, Mohammad; Bano, Shaher
The current study is the first substantial investigation to determine whether tinnitus perception mediates the relationship between physiological and psychological problems (PP). Simple random sampling, with a cross-sectional design, was used to collect data from 100 adult patients (males = 60; females = 40) diagnosed with chronic tinnitus. Subjects were approached through various public and private hospitals, at their respective Audiology and Ear, Nose, and Throat departments in Rawalpindi and Lahore, Pakistan. Participants underwent complete physiological and psychological tinnitus evaluations, such as tinnitus matching and audiometry, as well as assessments using standardized tinnitus instruments. The mediation analyses revealed an indirect relationship with hearing loss (HL) and PP (e.g., anxiety, stress, depression, mood swings) in tinnitus patients. These findings suggest that physiological problems such as tinnitus and HL might contribute to the development of psychological symptoms.